Pengembangan Konten MOOC Analisis dan Desain Algoritma Menggunakan Model Project Based Learning (PjBL) - Joko Samodra; Salsabila Thifal Nabil Haq; Luhur Adi Prasetya (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research aims to develop Massive Open Online Course (MOOC) content based on Project Based Learning (PjBL) in the Algorithm Analysis and Design course using the ADDIE development model. The focus of the research is to test the content validity, construct validity, and students' perceptions of project-based learning applied in MOOC. The results of validation by three experts showed that the developed content has an average Content Validity Index (CVI) above 0.85, which indicates that the content is in line with the learning objectives and consistent with the principles of PjBL. The implementation of PjBL-based MOOC was also proven to increase student engagement, where 82% of students reported higher active participation compared to traditional methods. In addition, 85% of students reported an increase in their understanding of the algorithm concepts, supported by the PjBL-based project that helped them apply the theory in a real context. Interactive learning media such as learning videos, online quizzes, and algorithm simulations also contributed to the high level of student satisfaction, with an average score of 4.1. Overall, the implementation of PjBL in MOOC content is effective in improving student engagement, understanding, and satisfaction, as well as providing a relevant and efficient online learning model for algorithm analysis and design courses.